2016
DOI: 10.1038/srep36323
|View full text |Cite|
|
Sign up to set email alerts
|

N-acetyl ornithine deacetylase is a moonlighting protein and is involved in the adaptation of Entamoeba histolytica to nitrosative stress

Abstract: Adaptation of the Entamoeba histolytica parasite to toxic levels of nitric oxide (NO) that are produced by phagocytes may be essential for the establishment of chronic amebiasis and the parasite’s survival in its host. In order to obtain insight into the mechanism of E. histolytica’s adaptation to NO, E. histolytica trophozoites were progressively adapted to increasing concentrations of the NO donor drug, S-nitrosoglutathione (GSNO) up to a concentration of 110 μM. The transcriptome of NO adapted trophozoites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 75 publications
1
48
0
Order By: Relevance
“…We have previously reported that OS induced by H 2 O 2 inhibits protein synthesis in E. histolytica (Shahi et al, ; Trebicz‐Geffen et al, ). The presence of proteins that are involved in translation among OXs, such as the elongation factor‐1 alpha and elongation factor 2, suggests that AF regulates the translation of proteins in the AF‐treated trophozoites.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously reported that OS induced by H 2 O 2 inhibits protein synthesis in E. histolytica (Shahi et al, ; Trebicz‐Geffen et al, ). The presence of proteins that are involved in translation among OXs, such as the elongation factor‐1 alpha and elongation factor 2, suggests that AF regulates the translation of proteins in the AF‐treated trophozoites.…”
Section: Resultsmentioning
confidence: 96%
“…The culture was continued for an additional 24 hr. The viability of the trophozoites untreated or treated with AF was determined by the eosin dye exclusion method (Shahi, Trebicz‐Geffen, Nagaraja, Hertz, et al, ). The experiment was performed in duplicates and repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we exposed E . histolytica trophozoites to the nitric oxide (NO) donor, S-nitrosoglutathione (350 μM for 120 minutes)[ 41 ]. We found that E .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of HA-tagged EcMDH in the trophozoites was confirmed by western blotting ( Fig 3A ) and detecting MDH activity in their whole lysates ( Table 2 ). When we compared the resistance of HA-tagged EcMDH trophozoites to H 2 O 2 -induced oxidative stress ( Fig 3B ) and trophozoites transformed with the pcontrol plasmid[ 41 ], we found that the sensitivity of the HA-tagged EcMDH trophozoites and the pcontrol trophozoites to H 2 O 2 -induced oxidative stress was identical. Incubation of the HA-tagged EcMDH trophozoites in presence of malate (2 mM) prior to their exposure to H 2 O 2 -induced oxidative stress did not increase their resistance to H 2 O 2 -induced oxidative stress ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation